A long way from home : - Brokaw, Tom (Random House Audiobooks, 2002)
A collection of memories and reflections. Tom Brokow speaks of growing up in the American heartland and of the people, the culture, and the values that have shaped his life. He describes his childhood and youth in South Dakota from 1940 to 1960 and his parents’ early lives during the twenties and thirties. He also reflects on the American experience, as he has lived and observed it, during the central decades of the twentieth century